Peran Dinas Koperasi Usaha Kecil Menengah Perdagangan Surabaya Memulihkan Dampak Pandemi Covid-19 Usaha Mikro Bulak - Diaz Virdani; Agus Widiyarta (Mahesa Research Center, 2022)
The Covid-19 pandemic has had a negative impact on the Indonesian economy. One of the sectors that has been affected is micro-enterprises, which results in lower incomes for micro-enterprises and the threat of bankruptcy. Therefore, local government initiatives are needed, in this The Office Cooperatives Small Medium Enterprises and Trade to overcome these problems. The purpose of this study was to determine the role of The Office Cooperatives Small Medium Enterprises and Trade Surabaya recovering impact Covid-19 pandemic on micro-enterprises in District Bulak Surabaya. The research method used is descriptive qualitative. Data obtained through observation, interviews, and documentation. The data analysis technique used in this research is interactive with data collection, data condensation, data display and conclusion drawing. The results show that The Office Cooperatives Small Medium Enterprises and Trade Surabaya has carried out well in recovering the impact of the Pandemic on Micro Enterprises in District Bulak Surabaya. Based on the results of the analysis, the role of The Office Cooperatives Small Medium Enterprises and Trade Surabaya refers to its role as facilitator, regulator and catalyst.